IMPLEMENTASI PROGRAM KOTAKU DI KELURAHAN GEDANGANAK - Fajar Madjid Ramadhan; Endang Larasati Setianingsih; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Slum settlements are a common problem that occurs in urban areas, these problems are closely related to population growth and population density, both aspects cause an increase in the number of residents which has an impact on the increasing need for housing. The imbalance of land with the needs of the population causes the emergence of dense and uninhabitable settlements. To that end, the Ministry of Public Works and Housing has implemented a policy for alleviating slums through the City Without Slums Program (KOTAKU), the program on a national scale, one of which is the City Without Slums Program in Gedanganak Village. This study aims to describe and analyze the implementation of the program as well as the driving factors and inhibiting factors for the implementation of the KOTAKU Program in Gedanganak Village. The research method used in this research is descriptive through a qualitative approach using primary and secondary data sources. In conducting research, researchers describe and describe more deeply the stages of program implementation which include the preparation stage, planning stage, implementation stage, and sustainability stage. The research was then analyzed using the Atlas.ti software tool, the results showed that the implementation of the KOTAKU Program in Gedanganak Village had been going quite well, but there were still some things that could be maximized, especially at the preparation stage, and the sustainability stage. The factors that support and hinder the implementation of the program are resources, community participation, and the attitude of the implementor.